Platform Liability and Innovation - Doh-Shin Jeon; Yassine Lefouili; Leonardo Madio (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study a platformâs incentives to delist IP-infringing products and the effects of holding the platform liable for the presence of such products on innovation and consumer welfare. For a given number of buyers, platform liability increases innovation by reducing the competitive pressure faced by innovative products. However, there can be a misalignment of interests between innovators and buyers. Furthermore, platform liability can have unintended consequences, which overturn the intended effect on innovation. Platform liability tends to increase (decrease) innovation and consumer welfare when the elasticity of participation of innovators is high (low) and that of buyers is low (high).
Keywords: K40; K42; K13; L13; L22; L86; 330; platform; liability; intellectual property; innovation